2021
DOI: 10.48550/arxiv.2108.07460
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Persistent Homology with Selective Rips complexes detects geodesic circles

Abstract: This paper introduces a method to detect each geometrically significant loop that is a geodesic circle (an isometric embedding of S 1 ) and a bottleneck loop (meaning that each of its perturbations increases the length) in a geodesic space using persistent homology. Under fairly mild conditions we show that such a loop either terminates a 1-dimensional homology class or gives rise to a 2-dimensional homology class in persistent homology. The main tool in this detection technique are selective Rips complexes, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The assumptions of our main results of this paper are much easier to verify and in some cases hold more generally. Overall, persistent homology in dimensions 1, 2, and 3 is known to encode some geodesic circles and shortest 1-homology basis by [16,19,21] (and now also by results of this paper), properties of thick-thin decomposition [4] and injectivity radius [15]. On a similar note, the systole of a geodesic space is detected as the first critical scale of persistent fundamental group [16].…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…The assumptions of our main results of this paper are much easier to verify and in some cases hold more generally. Overall, persistent homology in dimensions 1, 2, and 3 is known to encode some geodesic circles and shortest 1-homology basis by [16,19,21] (and now also by results of this paper), properties of thick-thin decomposition [4] and injectivity radius [15]. On a similar note, the systole of a geodesic space is detected as the first critical scale of persistent fundamental group [16].…”
Section: Introductionsupporting
confidence: 62%
“…The entire 1-dimensional persistent homology (and fundamental group) of geodesic spaces has been completely classified in [16,17]. Paper [19] (and also [21]) contains a local version of the result of this paper: if a subset A ⊂ X has a sufficiently nice neighborhood, then parts of its persistent homology embed into persistent homology of X. The technical assumptions of these results hold for loops a and c of Figure 1, but not b.…”
Section: Introductionmentioning
confidence: 99%
“…Using ideas of [12] we prove that 1dimensional persistence of Rips and selective Rips complexes are isomorphic up to reparameterization. This is in sharp contrast with higher-dimensional persistence [13]. To summarize, we prove that the reconstruction properties of selective Rips complexes closely resemble those of Rips complexes.…”
Section: Introductionmentioning
confidence: 55%
“…However, detections in dimensions 2 and above require geodesic circles to have wide neighborhoods adhering to certain geometric conditions. This technical requirement has been circumvented in [13] which demonstrated that arbitrarily small geodesically convex neighborhoods suffice to detect a geodesic circle using selective Rips complexes with two parameters. In particular, selective Rips complexes with two parameters are a modification of Rips complexes designed to detect many (in some cases all [14]) geodesic circles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation